Placebo effects in allergen immunotherapy—An EAACI Task Force Position Paper. Issue 3 (6th March 2021) - Pfaar, Oliver; Agache, Ioana; Bergmann, Karl‐Christian; Bindslev‐Jensen, Carsten; Bousquet, Jean; Creticos, Peter S.; Devillier, Philippe; Durham, Stephen R.; Hellings, Peter; Kaul, Susanne; Kleine‐Tebbe, Jörg; Klimek, Ludger; et al.
Abstract: The placebo (Latin "I will please") effect commonly occurs in clinical trials. The psychological and physiological factors associated with patients' expectations about a treatment's positive and negative effects have yet to be well characterized, although a functional prefrontal cortex and intense bidirectional communication between the central nervous system and the immune system appear to be prerequisites for a placebo effect. The use of placebo raises certain ethical issues, especially if patients in a placebo group are denied an effective treatment for a long period of time. The placebo effect appears to be relatively large (up to 77%, relative to pretreatment scores) in controlled clinical trials of allergen immunotherapy (AIT), such as the pivotal, double‐blind, placebo‐controlled (DBPC) randomized clinical trials currently required by regulatory authorities worldwide. The European Academy of Allergy and Clinical Immunology (EAACI) therefore initiated a Task Force, in order to better understand the placebo effect in AIT and its specific role in comorbidities, blinding issues, adherence, measurement time points, variability and the natural course of the disease. In this Position Paper, the EAACI Task Force highlights several important topics regarding the placebo effect in AIT such as a) regulatory aspects, b) neuroimmunological and psychological mechanisms, c) placebo effect sizes in AIT trials, d) methodological limitations in AIT trial design and e) potential solutions in future AIT trial design. In conclusion, this Position Paper aims to examine the methodological problem of placebo in AIT from different aspects and also to highlight unmet needs and possible solutions for future trials.